Analysing the Effectiveness of Omnichannel Marketing Strategies on Customer Experience in Jordan - Mohammad, Anber Abraheem Shlash; Al- Daoud, Khaleel Ibrahim; Mohammad, Suleiman Ibrahim Shelash; Hindieh, Ayman; qurneh, Majed; Vasudevan, Asokan; Zhou , Wen (Journal of Ecohumanism, 2024)
Omnichannel marketing has become one of the most critical research areas, as the interactions of customers over different contact channels have been becoming increasingly complicated. The study focuses on the effectiveness of omnichannel integration in driving customer satisfaction and loyalty, placing special emphasis on the mediating role of satisfaction. The research will be based on widely accepted frameworks and theories and will seek to establish how dimensions such as synchronization, accessibility, and consistency will affect the customers' experiences. In testing the relationships among the constructs, SEM analysed data from 357 respondents. The method included outer loadings, path coefficients, and mediating effects to establish the significance of various factors. Synchronization was noted as the most influential dimension of omnichannel integration and enhancing customer satisfaction significantly. The results further reveal that while omnichannel integration is not directly affecting customer loyalty, it is doing so indirectly through satisfaction. Secondly, customer satisfaction turned out to be the strongest predictor of loyalty, with an almost perfect explanatory power of its variance. Control variables, including age, gender, and income, were ineffective and thus signified that these findings apply to each and every group.Therefore, it concludes that satisfaction is the equity point that will enable well implemented omnichannel strategies to be transformed into loyal behaviours and that synchronization plays a leading role in shaping satisfaction. This indicates a better expectation of customers toward seamless and real time experiences. These findings provide valuable insight for organizations in refining their omnichannel approaches and offer a robust foundation for future research in the dynamics of customer experience and loyalty.